Innowacyjność jako czynnik wzrostu międzynarodowej konkurencyjności przedsiębiorstw - Jasińska, Agnieszka (Innovation: a determinant of increasing competitivenes of enterprises in the global market., 2005)
The article points the importance of innovations for the success of modern enterprises at the global market. The author of this article also tries to show, that a lot of Polish enterprises have to pay much more attention to that. The author proves that at the present time the innovations become one of the most important key success factors of a modem firm.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (3); 2005; nr 1093, s. 74-83